A Bilateral Tessier Number 4 and 5 Facial Cleft and Surgical Strategy: A Case Report - Shahin Abdollahi Fakhim; Nikzad Shahidi (Iranian Journal of Otorhinolaryngology, 2013)
Introduction: Tessier facial cleft is among the rarest facial clefts reported in literatures and there are many issues arguing about its multidisciplinary repairing techniques. Tessier number 4 and 5 are extremely rare facial anomalies. There are few literatures describing these clefts and their surgical modalities. Number 5 Tessier cleft begins medial to oral commissure in the upper lip and extends superiorly as a groove through the cheek and ends at the middle third of lower eyelid. Bonny involvement consists of alveolar ridge, maxillary bone lateral to infra orbital foramen and orbits lower rim and floor. Number 4 Tessier facial cleft begins between cupid bow and oral commissure; skirting the nose and pass through cheek and lateral to lacrimal duct. Bonny involvement consists of alveolar ridge, maxillary bone medial to infra orbital foramen and orbital rim and floor.   Case Report: This paper represents a patient with bilateral number 4 and 5 Tessier cleft lip with unilateral complete cleft palate and surgical approach on her.   Conclusion: We recommended early repair using autogenously tissues and minimal discarding healthy tissues as possible.